Establishing the Library Landscape in Europe: LIBER’s Portfolio of EU projects - Ayris, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
The purpose of this paper is to examine LIBER’s portfolio of EU projects, to analyse how/if these projects help deliver LIBER’s strategy, and to establish criteria for assessing the success of LIBER projects through the new LIBER project scorecard. The paper is a written version of the talk which the author gave at the 40th LIBER Annual Conference in Barcelona in 2011, a digital recording of which is also available.